한국전쟁 후 국가건설 시기의 정부 조직과 기능 변화에 대한 연구 -1948년부터 1960년까지를 중심으로 - 김정숙; 황창호; 이남국 (한국비교정부학보, 21(2), 2017)
This study assumed that the Korean War affected the national functions and institutions based on the contribution and limitations of the previous studies. I will examine four functions of consensus, production, integration and enforcement of central government organization and function after the Korean War according to Tilly and capitalism theory. Specifically, this study analyzed changes in four key functions of the government - consensus, production, integration, and enforcement - through changes in budgets, regulations, and decrees of government departments after the Korean War. As a result of analysis, after the Korean War, the government showed that the consensus function and the integration function were relatively strengthened compared to other functions. However, in terms of budget, the function of consensus and integration were strengthened, while the function of production was further strengthened in the aspect of regulation and decree, and it was confirmed that integration function was strengthened again in the late 1950s. This means that since the production function was needed among the national functions after the war, the related regulations and ordinances have increased sharply in order to carry out related tasks. On the other hand, in the context of the confrontation between the two Koreas, it meant that the system was stabilized by expanding the budget for the defense function, while at the same time expanding the budget for education and the like. KCI Citation Count: 0